Ultrastrong exciton-plasmon couplings in WS2 multilayers synthesized with a random multi-singular metasurface at room temperature - Wu, Tingting; Wang, Chongwu; Hu, Guangwei; Wang, Zhixun; Zhao, Jiaxin; Wang, Zhe; Chaykun, Ksenia; Liu, Lin; Chen, Mengxiao; Li, Dong; Zhu, Song; Xiong, Qihua; et al. (Nature communications, 2024)
Van der Waals semiconductors exemplified by two-dimensional transition-metal dichalcogenides have promised next-generation atomically thin optoelectronics. Boosting their interaction with light is vital for practical applications, especially in the quantum regime where ultrastrong coupling is highly demanded but not yet realized. Here we report ultrastrong exciton-plasmon coupling at room temperature in tungsten disulfide (WS 2 ) layers loaded with a random multi-singular plasmonic metasurface deposited on a flexible polymer substrate. Different from seeking perfect metals or high-quality resonators, we create a unique type of metasurface with a dense array of singularities that can support nanometre-sized plasmonic hotspots to which several WS 2 excitons coherently interact. The associated normalized coupling strength is 0.12 for monolayer WS 2 and can be up to 0.164 for quadrilayers, showcasing the ultrastrong exciton-plasmon coupling that is important for practical optoelectronic devices based on low-dimensional semiconductors. Here, the authors fabricate a metasurface with nanometre-sized plasmonic hotspots that interact coherently with WS 2 excitons, achieving ultrastrong exciton-plasmon coupling.